การพัฒนารูปแบบเสริมสร้างความสามารถในการคิดไตร่ตรองเชิงวิพากษ์ทางการสอนตามทฤษฎีการเรียนรู้เพื่อการเปลี่ยนแปลงและแนวคิดการพัฒนาบทเรียนร่วมกัน สำหรับครูบรรจุใหม่: A Model Development to Enhance Critical Reflection Thinking in Teaching Ability Through Transformative Learning Theory and Lesson Study Approach for Novice Teacher - Katiya, Krittiya; Kaewurai, Wareerat (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2023)
The purpose of this research was to develop a model for enhancing critical reflection thinking in teaching ability by using the research and development (R&D) process which consisted of 4 steps. The sample group was 17 novice teachers which is in the intensive development period of 2 years under the Nan Primary Education Service Area Office 1, acquired voluntarily. The study was conducted in 48 hours. Tools used in the experiment were a manual for using the model, and a test for critical reflection thinking in teaching ability. The data were analyzed using percentage, mean (), standard deviation (S.D.), Non Parametric Statistics Wilcoxon Matched-pairs Signed rank test, and content analysis. The findings are as follows. (1) The results of the study of basic information found that the organization of the activities was based on the principle of using groups to change, holistic change, learning from teaching problems, and understanding oneself. Regarding the techniques for organizing activities, the novice teachers should be able to organize activities and pay attention to designing teaching. For the method, the activities were organized into 2 periods: a preparation before practice in real situations and a practice in real situations. (2) The results of the build and quality check of a model found that the teacher development model developed by the researcher had 6 components: 1) principles 2) objectives, 3) content , 4) teacher development process 3 processes consist of 1 preparing and building a development team , 2 unite the power of learning to change and 3 exchanging knowledge to create new experiences 5) materials and learning sources, and 6) measurement and evaluation. The quality in terms of appropriateness was at a high level ( = 4.30, S.D. = 0.39). The result of using the model revealed an Effectiveness Index (E.I) of 0.5714. (3) The results of the experiment using the model found that the novice teachers who participated in the activities according to the model had significantly higher scores on the critical reflection thinking in teaching ability after than before development statistically at .05 level. (4) The results of the model evaluation in terms of input revealed that the activity planning was systematic. The processor was very knowledgeable and capable of carrying out activities very well. Location, materials, and time were readily conducive to organizing activities. The media and learning resources were readily available, diverse, and very useful for organizing activities. In terms of output, the novice teachers learned something new and changed their own views for teaching.